2008
DOI: 10.1088/0953-8984/20/22/224018
|View full text |Cite
|
Sign up to set email alerts
|

The photo-induced phase and coherent phonon in the organic conductor (EDO-TTF)2PF6

Abstract: We have investigated the nature of the photo-induced state and coherent phonon in the conducting charge transfer complex (EDO-TTF) 2 PF 6 by measuring the ultrafast reflectivity change over a wide photon energy range from 0.069 eV (18 μm) to 2.1 eV (580 nm). The photo-induced spectra just after photo-excitation indicate that the photo-induced phase is similar to but clearly different from that in a thermally induced metal phase though they are the same for general photo-induced phase transition. The temporal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…According to a previous report, the dynamical change in the spectral shape in the vis–IR region indicated that the lifetime of the (1010) charge-disproportionate phase is within 5 ps . The present results shown in Figure are closely consistent with this result.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…According to a previous report, the dynamical change in the spectral shape in the vis–IR region indicated that the lifetime of the (1010) charge-disproportionate phase is within 5 ps . The present results shown in Figure are closely consistent with this result.…”
Section: Resultssupporting
confidence: 93%
“…According to a previous report, the dynamical change in the spectral shape in the vis−IR region indicated that the lifetime of The Journal of Physical Chemistry C the (1010) charge-disproportionate phase is within 5 ps. 36 The present results shown in Figure 4 are closely consistent with this result. Therefore, we conclude that the fast decay process commonly observed at 1424 and 1572 cm −1 is due to electronic relaxation of the photoinduced (1010) phase.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is estimated that only one in 500–1500 molecules , is excited by such a pulse. How such a local event leads to a bulk phase transition is subject of speculation. , One possibility we see is the scenario in which a neutral bent molecule is excited to become planar. The geometry change could affect a neighbor molecule to also change geometry, thereby propagating the effect of the excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Such ultrafast oscillation of optical reflectivity is generated by the activation of coherent optical phonons, which modulate the dielectric susceptibility through electron-phonon coupling. The contribution of a specific phonon to optical modulation is photon energy dependent [33] and explains the apparent relative change of the spectral weight of the modes for measurements using 0.83 and 1.72 eV probes.…”
Section: A Coherent Phononsmentioning
confidence: 92%